The Influence of Lunar Phases on Complications in Cataract Surgery: An Analysis of 16,965 Patients - Eva-Maria Faschinger; Pia Veronika Vécsei-Marlovits; Dieter Franz Rabensteiner; Birgit Weingessel (Journal of Ophthalmology)
Purpose. Popular beliefs exert an impact of lunar phases on elective surgery. The aim of our study was to evaluate potential correlations between complications in cataract surgery and the phases of the moon during its passage through the zodiac and Fridays that fall on the 13th. Methods. Patients with complications during cataract surgery were extracted retrospectively from the clinical database from 2010 to 2014. The dates of surgeries were viewed in relation to the phase and the position of the moon (sign of the zodiac). Results. Of 16,965 cataract surgeries, 132 eyes developed complications. 0.70% developed complications with a waxing moon, and 0.87% with a waning moon (p=0.745). After Bonferroni correction, there were no statistically significant differences between the numbers of complications under the different signs of the zodiac and no complications on Fridays that fell on the 13th. Conclusions. The analysis of “non-moon-fitting days” for surgery showed quantitative differences, without statistically significant findings. Our results revealed more complications when the moon was waning, which is in contrast to esoteric belief. Patients may be informed that phases of the moon, signs of the zodiac, or a particular date will have no impact on their surgeries.